Chlamydia pneumoniae infection, complement factor H variants and age-related macular degeneration - Shen, D (2008)
BACKGROUND/AIMS: Impaired inhibition of the alternative complement pathway by complement factor H (CFH) is linked to age-related macular degeneration (AMD) based on the strong association between CFH variant and AMD. Chlamydia pneumoniae (C pneumoniae) infection can trigger the alternative pathway, but the evidence for an association between C pneumoniae and AMD is contradictory. This study investigated whether C pneumoniae infection is associated with AMD and whether the presence of C pneumonia modulates AMD risk conferred by CFH variants. METHODS: Genomic DNA extracted from peripheral blood of 148 advanced AMD patients and 162 controls was subjected to Taqman and PCR-RFLP for the CFH polymorphism and PCR for the C pneumoniae gene. Genomic DNA was also examined from microdissected macular cells from 59 AMD and 16 age-matched non-AMD archived slides. χ(2) testing was performed for case-control analysis. RESULTS: C pneumoniae infection was associated with increased risk of AMD (OR = 2.17, p<0.017). A CFH variant was also linked to increased risk of AMD (OR = 1.98, p<0.0001). However, no relationship was found between risk-conferring CFH variant and C pneumoniae (OR = 1.81, p = 0.08). CONCLUSION: There is a possible association between AMD and C pneumoniae infection, although CFH may not be directly involved in the pathogenesis of C pneumoniae infection-mediated AMD.